2023
DOI: 10.26599/jac.2023.9220743
|View full text |Cite
|
Sign up to set email alerts
|

Single-source-precursor derived SiOC ceramics with in-situ formed CNTs and core–shell structured CoSi@C nanoparticles towards excellent electromagnetic wave absorption properties

Abstract: In this work, novel carbon nanotube (CNT)/CoSi/SiOC nanocomposite ceramics with in-situ formed multi-walled CNTs and core-shell structured CoSi@C nanoparticles were successfully prepared via a single-source-precursor derived ceramic approach. Ppolymeric precursor characterization as well as phase evolution, microstructure, and electromagnetic wave (EMW) absorption properties of the ceramics were investigated in detail. The results show that the in-situ formed CNTs and magnetic CoSi@C nanoparticles provide a sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 54 publications
0
16
0
Order By: Relevance
“…As a result, they effectively promote multiple reflections and conductivity loss of EMWs within the ceramics, leading to a significant improvement in the EMW absorbing properties of PDCs. For instance, [14] the CNTs/CoSi/SiOC ceramic nanocomposites exhibit exceptional EMW absorbing properties in our previous work. The in-situ growth of highly conductive carbon nanotubes (CNTs) forms a conductive network, enhancing the interface and electrical conductivity of the ceramics.…”
Section: Introductionmentioning
confidence: 79%
“…As a result, they effectively promote multiple reflections and conductivity loss of EMWs within the ceramics, leading to a significant improvement in the EMW absorbing properties of PDCs. For instance, [14] the CNTs/CoSi/SiOC ceramic nanocomposites exhibit exceptional EMW absorbing properties in our previous work. The in-situ growth of highly conductive carbon nanotubes (CNTs) forms a conductive network, enhancing the interface and electrical conductivity of the ceramics.…”
Section: Introductionmentioning
confidence: 79%
“…5,6,11 Compositionally, PDCs with increased levels of free carbon and dielectric phases have been developed through managing pyrolysis conditions, 12 and employing a molecular approach with carbon-rich or metal-containing precursors. [13][14][15][16][17] For example, Yu et al reported a silicon oxycarbide nanocomposite with carbon nanotubes and cobalt silicide via a single-sourceprecursor derived ceramic method. This approach leverages the interactive contributions of both dielectric and magnetic losses.…”
Section: Introductionmentioning
confidence: 99%
“…This approach leverages the interactive contributions of both dielectric and magnetic losses. 13 Our recent work incorporated metal-organic frameworks into silicon carbonitride nanocomposite ceramics to regulate their dielectric genes, resulting in substantial lattice strain and ultradense lattice defects that induce intense interfacial and dipole polarizations. 18 Concurrently, unique multiscale structures such as nanospheres, 19 fibers, [20][21][22] aerogels, [23][24][25][26][27] and metamaterials [28][29][30][31] have been conceived and realized.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, inorganic membranes are gaining more and more attention due to their excellent mechanical strength [ 41 ], strong corrosion [ 42 ] and high temperature resistance. Polymer-derived ceramics, such as SiOC, SiCN and SiOCN, have attracted great interest due to their low-temperature ceramization, molecular design, good manufacturability and processability [ 43 , 44 , 45 ].…”
Section: Introductionmentioning
confidence: 99%